Investigating contextual influences on urban soundscape evaluations with structural equation modeling. (15th January 2021) - Tarlao, Cynthia; Steffens, Jochen; Guastavino, Catherine
Abstract: Previous soundscape research has shown a complex relationship between soundscapes, public space usage and contexts of users' visits to the space. Yet many of these findings are restricted to one study site at a time and may not generalize to a global understanding of urban sound environments. The present study is a comparative analysis of in situ questionnaires collected over four study sites in Montreal (N = 1429) in both French and English. At each site, the questionnaire included items from the Swedish Soundscape Quality Protocol and other soundscape variables, as well as person-related (age, gender, extraversion, noise sensitivity) and situation-related (social interaction) variables. We first tested measurement invariance between the French and English versions of the used soundscape questionnaire. We then investigated the influence of contextual factors (combining person-related and situation-related variables) on soundscape evaluations. The analyses confirmed the underlying conceptualizations of proposed soundscape assessment questionnaires, confirmed metric invariance between French and English questionnaires, and revealed significant influences of contextual factors on soundscape dimensions. Our analysis further suggests that younger people, women, and extraverted people occupy the public space more in groups, and that people in groups rate the soundscape as more pleasant and less eventful. Older people and women were found to be more sensitive to noise, and more sensitive people tended to perceive the soundscape as less pleasant and less monotonous. This research represents a critical step in rigorously assessing soundscape evaluation methods and establishes solid groundwork to build more complex models of contextual influences on soundscape evaluation. Highlights: People in groups rate the soundscape as more pleasant and less eventful. Noise-sensitive people perceive the soundscape as less pleasant and less monotonous. Similar loadings of soundscape factor model across French and English speakers.